Carrier-free prodrug nanoparticles based on lonidamine and cisplatin for synergistic treatment of breast cancer. (October 2022) - Yang, Lu; Li, Junnan; Guan, Zhaoyuan; Zhang, Jingwen; Wang, Xin; Tang, Rupei
Herein, we combined a derivative of cisplatin (CP) and the chemosensitizer lonidamine (LND) to design an amphiphilic prodrug, in which the ratio of LND to cisplatin was fixed at 2:1. Diaminedichlorodihydroxyplatinum (DH-CP) is a hydrophilic cisplatin derivative. Due to its appropriate amphiphilicity, this prodrug could self-assemble into stable nanoparticles (denoted as LNP-NPs). Under the action of excessive glutathione (GSH) in tumor cells, DH-CP could be reduced to cytotoxic cisplatin. In addition, the released LND could inhibit the metabolic process of tumor cells, and improving the sensitivity of tumor cells to cisplatin. In vitro studies demonstrated that LNP-NPs displayed significantly cytotoxicity on breast cancer cells, and the cell viability after co-incubation for 48 h (CP 16 μg/mL) were 18.77% (MCF-7) and 20.01% (EMT6), respectively. LNP-NPs could also significantly inhibit the growth of MCF-7 tumor-like spheroids, which were realized through the high coordination and cooperation between CP and LND. Therefore, the carrier-free drug delivery system based on LND and DH-CP is expected to achieve a good synergistic anti-tumor effect.